Culturally Responsive Teaching Approach: Does it Could Enhance Elementary Students’ Creative Thinking Skills in Mathematics Learning? - Annisa Nurramadhani; Yuyun Elizabeth Patras; Resyi Abdul Ghani; Rista Chamelia Anggraeni; Arin Fajar Sisworo (Universitas Pendidikan Ganesha, 2025)
The low level of students' mathematical ability requires a transformation of learning that emphasizes contextual understanding and application, one of which is through the integration of local wisdom into culturally responsive teaching.Assessment The research aim is to investigate how culturally responsive teaching (CRT) approach could enhance students’ creative thinking skills in elementary school. The method that is used is quantitative, quasi-experimental design with 52 fifth-grader students as subject, 26 students in each class. The classes are devided into experimental class (with CRT approach) and control class (without CRT approach). The creative thinking of students is tested by the 10 essays wit four aspects, namely fluency, flexibility, originality, and elaboration. Data were analyze by RASCH model approach to described person ability and differential item functioning to describe is there any influence between creative thinking and students’ ethnicity. The results show that students’ creative thinking in experimental class is improve rather than in control class. However, the fluency and flexibility aspect of students is well improved rather than originality and elaboration aspect which needs improvement. The students’ ethnicity has influence to their creative thinking, which other ethnicity outside Sundanese has high fluctuation in positive way. It could be concluded that culturally responsive teaching (CRT) can enhance students’ creative thinking skills and students’ ethnicity or cultural background influence their creative thinking skills.